Individual and team learning in a learning organization: A study of university libraries in Malaysia - Ahmad Kassim, Norliya; Mohd Nor, Azizah (2006)
This paper partly presents the results of a study being carried out at 12 university libraries in the Klang Valley of Malaysia. The study aims to investigate whether librarians are practising the concepts of a learning organization, and to examine their perceptions on the practices of individual and team learning in their workplace.The results of the study revealed that librarians perceived that there is an existence of learning practices at the individual and team level, but they are not too convinced of the extent to which the practices exist.